Physical Activity Behavioral Intervention for type 2 DM Patients: A Literature Review - Zainuddin, Zainuddin; Herlina Jusuf; Sarinah Basri K; Rosmin Ilham (PT Inovasi Pratama Internasional, 2023)
Various chronic and acute conditions as comorbid diseases are highly influential to the everyday life of type 2 diabetes mellitus patients, including in physical, psychological, economic, family burden, and quality of life aspects. The protocol and evaluation of this literature review used the PRISMA checklist. Using four databases; Pubmed, Science-direct, Scopus/Web of Science, and ProQuest. Five main physical activity behavioral intervention models for diabetes mellitus patients were discovered: 1. empowerment (individual and familial); 2. diabetes self-management education; 3. web-based digital health intervention; 4. motivational interviewing; and 5. SMS-based education. The five models focused on strengthening the importance of physical activity in diabetes mellitus patients’ self-management.